Features of tennis methods of teaching 5-6 years old children in the initial stages - Kurmaeva, E.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : theoretical and methodological justification for the existing teaching methods tennis of 5-6 years old children. Material : 17 special analysis and scientific and methodological sources. Results : the features of the existing methods of teaching children at an early stage of training. The main theses of the existing methods: 1) the training process is carried out in the form of games; 2 ) the level of general physical preparedness level exceeds special; 3) The first two years of the children do not participate in official competitions; 4) education of children begins with " School Ball ", with a gradual transition to employment with racket and ball; 5 ) training is built on two levels: theoretical - each " part" in the form of pre- formation of a mental model of rational behavior, and practical - the formation of the ability to perform motor actions. Conclusions : it was found that the existing methods of constructing the training process for children 5-6 years do not account for their physiological characteristics, therefore proposed to use computer technology and animation, that will shorten the formation of motor skills of children.